2013
DOI: 10.1136/gutjnl-2013-304833
|View full text |Cite
|
Sign up to set email alerts
|

A decrease of the butyrate-producing speciesRoseburia hominisandFaecalibacterium prausnitziidefines dysbiosis in patients with ulcerative colitis

Abstract: The composition of the fecal microbiota of UC patients differs from that of healthy individuals: we found a reduction in R hominis and F prausnitzii, both well-known butyrate-producing bacteria of the Firmicutes phylum. These results underscore the importance of dysbiosis in IBD but suggest that different bacterial species contribute to the pathogenesis of UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

71
955
4
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,452 publications
(1,116 citation statements)
references
References 49 publications
71
955
4
15
Order By: Relevance
“…2012; Machiels et al. 2014). A bidirectional relationship between an altered microbial community and the host perpetuates an inflammatory state that leads to further effects on the immune response and maintains states of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Machiels et al. 2014). A bidirectional relationship between an altered microbial community and the host perpetuates an inflammatory state that leads to further effects on the immune response and maintains states of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…IP was assessed by using the radioactive probe 51 Cr-EDTA as described previously (5). Briefly, after an overnight fast and emptying of the bladder, patients drank a Nutridrink (200 mL, 150 kcal/100 mL) (Nutricia) containing 50 μCi (1.85 MBq) 51 Cr-EDTA. Urine was collected for 24 h. Radioactivity was measured in urine collections with a gamma counter (Cobra5003; Canberra Packard).…”
Section: Methodsmentioning
confidence: 99%
“…1. Intestinal permeability was measured by using the 51 Cr-EDTA method. (A) Results revealed that, at T1, 26 of 60 patients had elevated gut permeability whereas the remaining 34 patients had normal gut permeability compared with control subjects.…”
Section: Ip Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to the abundance of specific organisms have also been associated with IBD. For example, a reduction in abundance of the butyrate-producing bacterium, Faecalibacterium prausnitzii is commonly seen in the setting of active inflammation, 10 , 11 whereas the abundance of Escherichia coli is commonly increased in active IBD.…”
Section: Introductionmentioning
confidence: 99%